Microglia: A Potential Drug Target for Traumatic Axonal Injury - Xin Huang; Wendong You; Yuanrun Zhu; Kangli Xu; Xiaofeng Yang; Liang Wen (Neural Plasticity, 2021)
Traumatic axonal injury (TAI) is a major cause of death and disability among patients with severe traumatic brain injury (TBI); however, no effective therapies have been developed to treat this disorder. Neuroinflammation accompanying microglial activation after TBI is likely to be an important factor in TAI. In this review, we summarize the current research in this field, and recent studies suggest that microglial activation plays an important role in TAI development. We discuss several drugs and therapies that may aid TAI recovery by modulating the microglial phenotype following TBI. Based on the findings of recent studies, we conclude that the promotion of active microglia to the M2 phenotype is a potential drug target for the treatment of TAI.